Effect of differentiated learning method on students’ motivation and achievement in learning Arabic as a foreign language - Meyad, Najiba Abdullah Mahdi (2014)
The purpose of this study was to examine the effects of Differentiated Learning Method (DLM) on students’ motivation and achievement towards studying Arabic Language (AL) as a foreign language for non-native speakers. The participants in this study were 100 (47 males and 53 females) form four Malaysian students in secondary school from Kolej Islam Sultan Alam Shah (KISAS). This study applied a quasi-experimental design. The instruments employed were demographics questionnaire, the motivation questionnaire, and the AL achievement tests to determine the students’ motivation and achievement towards studying AL (writing, reading, grammar). For this purpose, the researcher taught two different groups. The first group, which is the experimental group, was taught by using DLM. The other group which is the control group was taught by using Teacher-Centered Method (TCM). A descriptive and inferential statistics were used to analyze the collected data in this study using SPSS software. An analysis of covariance (one-way ANCOVA) was conducted to compare the students' achievement in AL based on the post-test scores in the aspects of interpretive reading, writing, and grammar between the control and experimental groups while statistically controlled the pre-test effect. Furthermore, the independent sample t-test was used to compare the students’ motivation based on the post-test scores in the aspects of attainment value, extrinsic value, intrinsic value, study habit, cost value, expectancy for success, and ability belief between the experimental and control groups. In addition, Paired sample t-test was conducted to compare the effect of (DLM) on the achievements of the students while learning AL based on the pre-test and post-test scores in one group. In short, this study found that using DLM helped students perform and achieve significantly better than the control group while learning AL writing, reading, and grammar. The mean score in reading for the experimental group (M=20.04, SD= 4.43) was higher than the mean scores for the control group (M=18.38, SD= 4.69); t (1.82); p<.05). The same results have been found in grammar, the mean score for the experimental group (M=24.02, SD= 6.07) was higher than the mean scores for the control group (M=19.28, SD= 7.66); t (3.42); p=.00). Also, the mean score in writing for experimental groups (M=10.14, SD= 2.79) was higher than the mean score for the control group (M=8.20, SD= 2.38); t (3.73); p=.00). In addition, the students using DLM were obviously more motivated towards learning AL (M=155.74, SD= 12.66) than the students using TCM (M=145.28, SD= 14.41); t (3.85); p<.05) in the aspects of attainment value, study habit, extrinsic value, intrinsic value, cost value, expectancy for success, and ability belief. Finally, this research provides evidence that using DLM improved students’ motivation and achievement towards studying AL as a foreign language.